Visual expression of liberal education mission - Schimek, Gwendolyn Patricia, author; McKelfresh, David, advisor; Oldham, Kyle, committee member; Elkins, Becki, committee member; Siller, Thomas, committee member (Colorado State University. Libraries, 2016)
The purpose of this photo elicitation study was to explore the experience of undergraduate students in the Midwest attending liberal arts campuses. Using the American Association of Colleges and Universities’ four liberal education outcomes, the study asked student participants at four different liberal arts campuses to take photographs of the visual expression of these outcomes on their campuses over a 4-week time period. Additionally, participants took part in a focus group on their respective campus to discuss the photographs and begin to assign meaning to the photographs. The 19 participants in this study shared insights into their experiences at college and the ways they saw the liberal education outcomes expressed. The emergent themes reflected the following observations: (a) Relationships comprised community, and the nature of campus, support, and friendship was student focused; (b) Environment and physical space played a role in the student experience; (c) Campuses provided a well-rounded, integrative, and interdisciplinary student experience; (d) Students viewed themselves as partners, not consumers in the fabric of campus; and (e) An uncapturable component, which included residential campus and classroom experiences, was also present and created an important student experience.